2006
DOI: 10.1007/s10208-005-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Newton–Hensel Interpolation Lifting

Abstract: The main result of this paper is a new version of Newton-Hensel lifting that relates to interpolation questions. It allows one to lift polynomials in Z[x] from information modulo a prime number p = 2 to a power p k for any k, and its originality is that it is a mixed version that not only lifts the coefficients of the polynomial but also its exponents. We show that this result corresponds exactly to a Newton-Hensel lifting of a system of 2t generalized equations in 2t unknowns in the ring of p-adic integers Z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…Avendaño, Krick and Pacetti [2] obtain a heuristic algorithm for the interpolation of polynomials in Z[X ], with a complexity polynomial in h, log(d),h, p, whereh is a bound on the heights of A(y i ), for some suitable evaluation points y i ∈ Z, and where p is a ''lucky'' prime greater than τ . However, the probabilistic aspects are not…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Avendaño, Krick and Pacetti [2] obtain a heuristic algorithm for the interpolation of polynomials in Z[X ], with a complexity polynomial in h, log(d),h, p, whereh is a bound on the heights of A(y i ), for some suitable evaluation points y i ∈ Z, and where p is a ''lucky'' prime greater than τ . However, the probabilistic aspects are not…”
Section: Previous Workmentioning
confidence: 99%
“…To state it, we use the O˜( ) notation, so as to omit logarithmic factors: 2 + n 4 τ 4 log(d) 3 ) operations in S and a similar number of bit operations.…”
Section: Introductionmentioning
confidence: 99%
“…Avendaño, Krick and Pacetti [4] studied sparse polynomial interpolation over Z [x] and C[x]. They developed a new version of Newton-Hensel lifting specifically for interpolation questions.…”
Section: Introductionmentioning
confidence: 99%
“…They developed a new version of Newton-Hensel lifting specifically for interpolation questions. For t-sparse polynomial f ∈ C[x] represented by straight line programs of length L, Avendaño et al [4] found an algorithm which interpolates such f in time O(t 4 L). Also, they studied interpolation over (Z/pZ)[x].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation